O trabalho da criança e do adolescente no ordenamento jurídico brasileiro: normas e ações de proteção - Carvalho, Luciana Paula Vaz de (2010)
The exploration of the child and teenage labor represents one of the most concerning issues in the contemporary world. Therefore, this research intended to present the legal protection available in the Brazilian law for children and teenagers. The study of what is infantile and juvenile labor deserved special attention so as to better define and guide the protection norms. The survey of international covenants for child and teenage protection that Brazil ratified, as well as the study in comparative law, confirm the special attention that Brazil has been paying to this major social problem, adopting important protection instruments, amongst them the Federal Constitution, the Child and Teenage Statute and the Labor Law Consolidation. Such legal and protective framework is extremely important in view of the sad reality thousands of children and adolescents live in our Country, predominantly in domestic, rural and urban labor. In this scenario, several child labor eradication and teenage labor protection programs are being developed, with quite positive results and with the support of government agencies, non-government entities and the private initiative, without overlooking the important role that the Labor Prosecutors Office play in emancipating such children and teenagers, lost in a life without their childhood or youth